Les monnaies virtuelles décentralisées sont-elles des dispositifs d’avenir ? - Ariane Tichit; Pascal Lafourcade; Vincent Mazenod (Revue Interventions Économiques)
In this paper we argue that decentralized virtual currencies can contribute to systemic change driven by SSE. We first show that they cumulate a number of the strengths of local currencies and SELs in their transformative power and provide solutions to some of their weaknesses, while obviously having their own limitations. Secondly, we emphasize that there is a great diversification within crypto-currencies and that some of them are now developing energy-saving protocols that are more useful to the community or based on cooperation, while others serve projects close to SSE. The fusion of these projects, that have a priori opposed values, could therefore create a movement of sufficient magnitude to begin to represent a true counter-power. However, we have some criticisms of these devices and finally propose an idea of crypto-coin with geolocalized demurrage that could meet certain limits encountered especially by local currencies in their definition of proximity.